2013
DOI: 10.1111/jscm.12014
|View full text |Cite
|
Sign up to set email alerts
|

Does Socially Responsible Supplier Selection Pay Off for Customer Firms? A Cross‐Cultural Comparison

Abstract: Building on Carter and Jennings' (2002a,b, 2004) seminal works on socially responsible purchasing and logistics, this multinational study investigates the extent to which socially responsible supplier selection (SRSS) is associated with customer firms’ financial performance in three key world economic regions. We collect and utilize a unique dataset consisting of a total of 479 manufacturing, retail, and service provider firms operating in three distinct national cultures: China, the United Arab Emirates, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 103 publications
1
95
1
1
Order By: Relevance
“…OHSAS 18001, health and safety incidents, standardized health and safety conditions and health and safety practices are the identified sub-criteria for this main criterion (Ghadimi et al, 2015). In studies conducted in China (W. Yu et al, 2012;Yuan et al, 2012), the importance of selecting suppliers that consider safety-related behaviours and safety standards in their workspaces is emphasized due to a significant increase in industrial accidents and work-related injuries (Thornton et al, 2013).…”
Section: Health and Safety (Social)mentioning
confidence: 99%
See 4 more Smart Citations
“…OHSAS 18001, health and safety incidents, standardized health and safety conditions and health and safety practices are the identified sub-criteria for this main criterion (Ghadimi et al, 2015). In studies conducted in China (W. Yu et al, 2012;Yuan et al, 2012), the importance of selecting suppliers that consider safety-related behaviours and safety standards in their workspaces is emphasized due to a significant increase in industrial accidents and work-related injuries (Thornton et al, 2013).…”
Section: Health and Safety (Social)mentioning
confidence: 99%
“…Culpan and Guglielmo (2010) stated that SC globalization could have direct impact on awareness and human rights treatments for workforces in geographically dispersed suppliers. Thornton et al (2013) identified this matter as an important focus by manufacturing firms in seeking for suppliers that paying attention to human right issues such as discrimination are being highly established as an organizational mind-set.…”
Section: Employment Practices (Social)mentioning
confidence: 99%
See 3 more Smart Citations